Improved method for purification of enterotoxin from Clostridium perfringens type A. - Granum, P E (1980)
The purification procedure of Clostridium perfringens type A enterotoxin has been improved. The cell sonic extract was precipitated twice with ammonium sulfate, first 40% saturated to concentrate the enterotoxin and then 15% saturated. The two precipitations were followed by gel filtration on Sephadex G-100. The enterotoxin appeared to be homogeneous on 7% polyacrylamide gel electrophoresis after this three-step purification procedure, with a recovery of 56% and a 12.3-fold purification. The solubility properties at different pH values, temperatures, and ammonium sulfate concentrations are also given as basis for the purification procedure.